2014
DOI: 10.1108/bfj-12-2012-0308
|View full text |Cite
|
Sign up to set email alerts
|

Valuing country of origin and organic claim

Abstract: Purpose – The purpose of this paper is to identify and quantify the factors determining the prices of organic and conventional cheese. For a market with a high degree of product differentiation, i.e. the German cheese market, price premiums of various cheese attributes are examined. Thereby, special attention is paid to country of origin (CO) effects, geographical indications (GIs) and organic claims. Design/methodology/approach – The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Cuneo was the district from which the largest number of products originated at large-scale retail traders, whereas for farmers’ markets it was the province of Turin that most reflected direct sales and short supply chains. The short supply chain, in addition to ensuring a sustainable, higher quality, and more secure product [48,49,50], guarantees small producers market access with a seasonal product, even without consistent quality not conforming to the standard required by large-scale retail distribution [38]. The absence of Cuneo producers among those interviewed at farmers’ markets could be related to the structural differentiation and the production systems of goat farms in the different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Cuneo was the district from which the largest number of products originated at large-scale retail traders, whereas for farmers’ markets it was the province of Turin that most reflected direct sales and short supply chains. The short supply chain, in addition to ensuring a sustainable, higher quality, and more secure product [48,49,50], guarantees small producers market access with a seasonal product, even without consistent quality not conforming to the standard required by large-scale retail distribution [38]. The absence of Cuneo producers among those interviewed at farmers’ markets could be related to the structural differentiation and the production systems of goat farms in the different areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on food quality labels have used different methodological approaches (cluster analysis, factor analysis, conjoint analysis) (Schröck, 2014(Schröck, , pp. 1070(Schröck, -1091Balogh et al, 2016, pp.…”
Section: Methodsmentioning
confidence: 99%
“…2508(Sadilek, -2523.Several studies confirmed that EU quality labels and other labels displaying information on the place of origin, specific production methods and composition may play an important role in willingness to pay, communicating credence attributes of food products and influence consumers' purchase decisions (de-Magistris & Gracia, 2016, pp. 560-571;Erraach et al, 2014, pp.11-14;Schröck, 2014Schröck, , pp. 1070Schröck, -1091.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to D3, this definition does not include the potential differences between the organic and the conventional products (v OB and v CB can be equal or different, this is not taken into consideration). This operational definition is represented by Zhang et al [109], Smith et al [110], Schröck [111], Gerrard et al [112], Connolly and Klaiber [113], Schröck [114], Ankamah-Yeboah et al [115], Hoang et al [116], Monier-Dilhan and Bergès [117], Ay et al [118], Gschwandtner [119], and Schäufele and Hamm [120].…”
mentioning
confidence: 99%